A Portrait of the Monster as Criminal, or the Criminal as Outcast: Opposing Aetiologies of Crime in Mary Shelley’s Frankenstein - Léger-St-Jean, Marie (Romanticism and Victorianism on the Net, 2012)
This article offers a criminological reading of Mary Shelley’s Frankenstein based on the 1831 edition. It discusses the opposition between Dr. Victor Frankenstein’s physiognomic prejudice and the creature’s discourse designating social exclusion as the cause of its mischief. Frankenstein’s accusations rely mostly on its creation’s appearance, borrowing from Johann Kaspar Lavater’s principles. The monstrous creature counteracts its maker’s presumptions by interpreting its own criminal behaviour similarly to Christian Wolf’s self-analysis in Schiller’s short story “Der Verbrecher aus Verlorene Ehre.” A close reading of the circumstances of each of the monster’s four crimes demonstrates how deeply its criminality is interlocked with social rejection caused by its own external deformity. Both perspectives adapt tropes that can be found in criminal biographies still reprinted in the 1810s. Though both positions are credible, I argue that the storyline supports the creature’s view that the criminal might be a monster, but created by those it vengefully hurts. Throughout, I indicate when changes to Shelley’s 1816-1817 draft were made to arrive to the 1831 wording, paying also attention to who effected them.